Preliminary study on the maintenance level of waqf properties: federal territory, Kuala Lumpur - Bello, Hafis; Ayob, Mohd Fairullazi; Ahmad Sarkawi, Azila (UTM Press and managed by Islamic Civilization Academy, Faculty of Social Science and Humanities, Universiti Teknologi Malaysia, 2020)
There has been a growing interest in the development of income-generating Waqf (endowments) properties in recent times. This is quite justifiable considering the fact that Waqf properties estimated to worth up to USD 1 Trillion globally have failed to generate adequate income to meet up the maintenance costs thus resulting in poor maintenance and the inability of these properties to meet Waqf objectives. Consequently, this paper presents preliminary findings on an on-going research aimed at developing a maintenance management framework for income-generating Waqf properties. Data were gathered through content analysis and secondary sources. Findings in this paper indicate that the inadequate maintenance of Waqf properties is partly due to relatively low rents and high rental arrears. The paper also gathered that despite the unique features of Waqf, there is no specific study aimed at developing a user-driven maintenance management framework for income-generating Waqf properties. Such omission could slow down the much-anticipated progress particularly at this point in time when different funding initiatives have resulted in the construction of high-rise income-generating properties on Waqf lands. The paper also provided current information on the state of income-generating Waqf properties in Kuala Lumpur.